EKSPLORASI ZAT WARNA ALAMI DARI KULIT KAYU TINGI (Ceriops Tagal) DENGAN VARIASI TEKNIK PEMORDANAN - Atina Khoiron Nisa; Aminatur Rosyidah (Program Studi Kimia, Fakultas MIPA, Universitas PGRI Banyuwangi, 2026)
Natural dyes derived from plant materials have attracted increasing attention as environmentally friendly alternatives to synthetic dyes in the textile industry. One potential natural dye source is the bark of the tingi tree (Ceriops tagal), which is known to contain tannin compounds capable of producing brownish color on textiles. This study aimed to determine the optimal mordanting technique in the dyeing process of cotton fabric using tingi bark extract. The research employed an experimental laboratory approach by applying three mordanting techniques, namely pre-mordanting, meta-mordanting, and post-mordanting, using alum as a mordant. The extract was obtained through a decoction method and applied to cotton fabric through repeated immersion. Color quality was evaluated through visual assessment by 15 panelists and color fastness testing against washing using staining scale and grey scale according to SNI ISO 105-C06-2010. The results showed that the meta-mordanting technique produced the most intense and uniform color with an average panelist score of 4, higher than pre-mordanting and post-mordanting techniques. Color fastness to washing also indicated better performance with values ranging from 3 to 4. Statistical analysis using the Friedman K-Related Samples test showed a significance value of 0.000 (p < 0.05), indicating a significant difference among the mordanting techniques. These findings suggest that the meta-mordanting technique is the most effective method for improving dye absorption and color stability in cotton fabrics dyed with tingi bark extract, supporting its potential application in sustainable textile dyeing processes.